Study of Awareness and Performance of Ahvazi Midwives about Physiologic Childbirth in Public Hospitals, 2016 - pazandeh, Farzaneh; Kord, Mozhgan; afshari, poorandokht; Haghigizadeh, Mohamaad Hosein (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: To promote normal childbirth the care during childbirth should be on evidence-based care. Evidence-based care practices promote physiological birth and midwives. This study studied midwives’ awareness and performance about physiological childbirth in Ahvaz publiv maternity services. Methods: This descriptive study was conducted on maternity units in which 128 midwives were recruited using census sampling. The researcher made questionnaire were used for self-reporting of awareness and performance of midwives. Results: Majority of midwives (86.7%) had Bachelor degree, had (1-7) year’s work experience (64.1). This study showed that the Ahvazi midwives had relatively good awareness of physiologic labour items however the performance of them was not as ideal as their awareness. Conclusions: Iranian midwives are informed about evidence-based practice in childbirth which indicates that attempts to promote physiologic childbirth has been useful, however multifaceted implementation strategies are necessary to promote the use of evidence-based practice in clinical practice and health care decision making during labour childbirth.